Improving Students’ Writing Skill by Using Wholesome Scattering Game - Novrieta, Dina; Nurisa, Sopi (EEdJ: English Education Journal, 2021)
The aim of this research is to describe the implementation of Wholesome Scattering Game in improving students’ writing skills on descriptive text and to find out whether there is a significant difference between students who were taught by using Wholesome Scattering Game and the students who were not. This research used quantitative approach focusing on experimental research which was conducted at SMAN 2 Sungaiselan in academic year 2019/2020. The researcher used purposive sampling technique and two classes were taken as samples, with 69 students (35 students for the control group and 34 students for the experimental). The result of the test was analyzed by using statistical analysis of Paired sample t-test and Independent sample t-test. The finding showed that the students who were taught by using Wholesome Scattering Game got higher score than those who were taught by using non-Wholesome Scattering Game. It means that the alternative hypothesis (Ha) was accepted, while the null hypothesis (Ho) was rejected. It could be concluded that there was a significant difference between students who were taught by using Wholesome Scattering Game and the students who were taught without using Wholesome Scattering Game.